2013
DOI: 10.17660/actahortic.2013.979.47
|View full text |Cite
|
Sign up to set email alerts
|

Developing Genetic Mapping and Marker-Assisted Breeding Techniques in Bambara Groundnut (Vigna Subterranean L.)

Abstract: Bambara groundnut (Vigna subterranea L. (Verdc.)) is an underutilised African legume crop which shows a high degree of drought tolerance. It continues to be an important leguminous crop in tropical Africa and is grown mainly by women who are small-scale farmers in Africa under traditional low input agricultural systems. It is grown mainly for its protein and carbohydrate, as a fixer of agricultural nitrogen and for its high levels of drought tolerance. Genetic studies into this species could provide important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Over the past twenty years, various molecular markers for analyzing genetic diversity, specifically designed for Bambara groundnut, were documented to either oppose or validate the reports on phenotypic descriptors (Table 3; [93]. Numerous studies have discussed ways that molecular markers can: offer information and knowledge on genetic diversity in Bambara groundnut [93], determine heterozygosity for the purification of seed [94], link germplasm to specific features such as the geographic region [45], function in quality regulation and can be useful in realizing breeding objectives [77]. Similarly, various studies have been conducted to explore the genetic mechanism of significant traits, such as leaf appearance, stress tolerance [95,96] and can provide a basis for the comparison of crops, with and without complete genome sequences, to pave the way for the translation of positional data into underutilized crops [97].…”
Section: Genetic Diversity In Bambara Groundnutmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the past twenty years, various molecular markers for analyzing genetic diversity, specifically designed for Bambara groundnut, were documented to either oppose or validate the reports on phenotypic descriptors (Table 3; [93]. Numerous studies have discussed ways that molecular markers can: offer information and knowledge on genetic diversity in Bambara groundnut [93], determine heterozygosity for the purification of seed [94], link germplasm to specific features such as the geographic region [45], function in quality regulation and can be useful in realizing breeding objectives [77]. Similarly, various studies have been conducted to explore the genetic mechanism of significant traits, such as leaf appearance, stress tolerance [95,96] and can provide a basis for the comparison of crops, with and without complete genome sequences, to pave the way for the translation of positional data into underutilized crops [97].…”
Section: Genetic Diversity In Bambara Groundnutmentioning
confidence: 99%
“…On average, a yield of 0.85 t ha −1 is achievable in Bambara groundnut [50]; however, the crop has been reported to have a genetic potential to produce up to 4000 kg ha −1 [106]. Reports by Somta et al [94] and Molosiwa et al [76] advocated Bambara groundnut being individual plants that are extremely inbred. Nevertheless, farmer landraces are quite a mixture of (mostly related) inbred lines and molecular evaluation, and this has shown that this condition persists even amongst the released varieties [107].…”
Section: Research To Datementioning
confidence: 99%
See 2 more Smart Citations
“…Verdc , 2 n = 2 x = 22) is a nutritionally rich, underutilised, indigenous African legume crop and mainly grown for its protein rich seed. This crop continues to be the third most important food legume crop after groundnut and cowpea in semi-arid Africa [ 1 , 2 ]. Due to its good seed nutritional values, particularly for the protein component in developing country diets, bambara groundnut has been receiving increased interest and could undergo a shift from subsistence crop to a cash crop i.e., bambara groundnut has been canned at a commercial level [ 3 ].…”
Section: Introductionmentioning
confidence: 99%